Ocorrência de fatores associados à hipotermia no intraoperatório - Prado, Carolina Beatriz Cunha (2015)
Hypothermia is one of the adverse events with the highest incidence among surgical patients in the intra and post-operative periods. This research aimed to analyze the occurrence and the social-demographic, clinical and laboratory (blood glucose) factors associated with hypothermia during surgery in patients undergoing elective abdominal surgery. This is an observational, cross-sectional, analytical study with a quantitative approach of the data. This study was approved by the Ethics in Research Committee of the Federal University of Triângulo Mineiro (UFTM) under the opinion: 667.693/2014. The data was collected in the Surgical Block of UFTM's Clinical Hospital using an instrument that included social-demographic and clinical variables of patients and variables related to the anesthetic-surgical procedure and the environment of the Operating Room (OR). The ones who participated in this study were patients who underwent conventional abdominal and/or minimally invasive elective surgery, 18 plus years old of both genders and with ASA classification I and II, adding up to a total of 105 (n) patients. The qualitative variables were analyzed using descriptive statistics, and for the quantitative, descriptive measures of centrality and dispersion were used. The chi-square test was used to associate the variables gender, age, BMI and blood glucose in the admission at the OR, blood sugar after surgery, ASA, surgical approach and the use of preventive measures with the presence of hypothermia. To correlate the occurrence of hypothermia with the type of anesthetics, we used ANOVA. Using Pearson's correlation coefficient, we verified the correlation between the average temperature variable of patients in the period with the following variables: duration of the surgical anesthetic period; stay time in the OR and average temperature in the OR.The level of significance in this study was p<0.05. It was found that most of the patients studied were females 73 (69.5%), adults 85 (81%), classified as overweight 54 (51.4%) and ASA II 51 (48.6%). There was greater proportion of the patients who underwent general anesthesia 61 (58.1%) and surgical approach with minimal invasion 56 (53.3%). The most adopted surgical positioning was the supine position 49 (46.7%) and the prevalent type of surgery was cholecystectomy 38 (36.2%). Hypothermia occurred in 98 (93.3%) patients. Only 2 (1.9%) patients received some form of heating measure. In terms of complications during surgery, 9 (8.6%) patients had hypotension and 1 (1%), besides hypotension, bradycardia. The glucose changes in the admission at the OR were not predictive for the occurrence of hypothermia. The hypothermia was not a statistically significant factor to predict the incidence of hyperglycemia at the end of the anesthetic-surgical procedure nor the occurrence of complications during surgery. There was no significant correlation between the average temperature of the patient and the average temperatures of the OR. The variable female gender was statistically significant for predicting hypothermia, as well as combined anesthesia, duration of the anesthetic-surgical procedure and length of stay in the OR. We can highlight the importance of new studies that may be able to assess the effectiveness of preventive measures for hypothermia and so add scientific evidence for clinical practice.